THE IMPLEMENTATION OF MIND MAPPING TECHNIQUE BY USING WEBLOG IN IMPROVING STUDENTS’ ISLAMIC WRITING: ACHIEVEMENT AND INSIGHT - Apriani, Eka; Labiran, Roni; Esmianti, Farida; Syafryadin, Syafryadin; Supardan, Dadan (English Review: Journal of English Education, 2022)
The goals of this study were to learn about students' perspectives on literature and blogs for teaching Islamic values to the millennial generation. This research was mixed-methods research. The subject of this study was the millennial generation at the Islamic State Institute Curup, especially students of the English Tadris Study Program. The instruments were questionnaires and interviews. This study included 30 students as participants. The findings of the poll reveal that most students have a favourable view of the use of the mind-mapping approach by utilising weblogs to improve Islamic writing. The implementation of the mind-mapping technique by using a weblog to improve Islamic writing makes students more active and interested in learning Islamic topics. Students also understand more about some Islamic topics that they read or upload to their web blogs. Students are interested in learning more about Islam by using this media. They read more topics about Islam and give their opinions about those in their Islamic literature web blog. It may be stated that a blog can be used as a form of social media and is effective and positive for teaching Islamic values to students.